Imagining Critical Pedagogies and Ecological Humanities in the Pluriverse: Nomadic, Decolonial and Life-Centered Environmental Education as a South-Complex Environmental-Desiring Machine - Garcia-Arias, Jorge; Pessoa Brandão, Helen Moura; Sanchez Gomez, Natalia (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
Our article explores the possibilities of imagining a decolonial environmental education in Abya Yala/Latin America as an environmental-desiring machine underpinned by a South-complex environmental thinking, capable of generating subjectivations, promoting agency, and nurturing critical pedagogy praxes that place ecosystems sustainability and care-of-life at the very center. To illustrate those pluriversal alternatives, we present two educational and political-pedagogical experiences: a ‘nomadic curricula’ praxis on the Federal University of Espírito Santo (Brazil) mediated by (re)existence/resistance movements woven by Kapi’xawa and Kizomba collectives and communities; and a water-care popular environmental education experience in the Sochagota Lake (Colombia), as a pedagogical praxis of (re)existence/resistance to hegemonic market-episteme ‘water management’ models.